Workforce Diversity and Employee Performance in the Higher Education Sector in Kathmandu - Lama, Padam Bahadur; Lamichhane, Basu Dev; Niroula, Arjun Kumar; Hamal, Janga Bahadur; Pant , Ganesh Datt; Ojha , Hari Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: Workforce diversity with better management fosters employee performance. The research aims to assess the effect of workforce diversity comprising gender diversity and diversity at the academic level on employee performance. Methods: The research employed a descriptive and causal research design. The primary sources of data utilized in the study. This research utilized a purposive sampling technique. The population of the study was faculty members of the higher education sector in Kathmandu. Thus, a structured questionnaire of 377 was disseminated to the target respondents and received only 191 useful questionnaires. Moreover, the research utilized descriptive statistics, correlation, and regression for data analysis. Results: The findings of the research revealed a positive influence of gender diversity on performance (β = 0.114; t = 1.27), however, it was found insignificant. Moreover, a positive and statistically significant effect of diversity at the academic level was found on employee performance (β = 0.774; t = 8.87). Conclusion: The management of workforce diversity in the higher education sector fosters the performance of faculty members reflecting that academic institutions embracing inclusive steps from the recruitment process to cultivate a diverse workforce to enhance performance. Novelty: This research discovers the evidence boosting employee performance linking the diverse workforces especially gender diversity and diversity at the academic level deriving the evidence from the higher education sector. The findings of this research establish a benchmark for advancing the performance of employees.